Civil society and public sector institutions: more than a zero-sum relationship - Uphoff, Norman; Krishna, Anirudh (2004)
Measuring civil society strength has become entangled in competing definitions of civil society (CS). A more productive approach begins by considering CS from the perspective not of what it is but from what it does. Civil society functions - articulating citizens' interests and demands, defending their rights and meeting their needs - can be performed by a vairety of institutions and organisations, not all of which are or need to be detached from the government. Determining the strength of CS requires assessing how well these functions are performed by a continuum of organisations and institutions. A disaggregated, multi-sector model is developed that assists in measuring CS strength if any specific context. - Reproduced.
Keywords: Civil society